2013
DOI: 10.1371/journal.pone.0061075
|View full text |Cite
|
Sign up to set email alerts
|

Co-Variation between Seed Dormancy, Growth Rate and Flowering Time Changes with Latitude in Arabidopsis thaliana

Abstract: Life-history traits controlling the duration and timing of developmental phases in the life cycle jointly determine fitness. Therefore, life-history traits studied in isolation provide an incomplete view on the relevance of life-cycle variation for adaptation. In this study, we examine genetic variation in traits covering the major life history events of the annual species Arabidopsis thaliana: seed dormancy, vegetative growth rate and flowering time. In a sample of 112 genotypes collected throughout the Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
171
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(194 citation statements)
references
References 84 publications
(117 reference statements)
14
171
3
1
Order By: Relevance
“…In that case and here in this study, high FT levels are associated with the low dormancy state. A recent study of natural variation in Arabidopsis also showed that late flowering is correlated with higher seed dormancy (38). Again this shows that late flowering is associated with more dormant states, in agreement with our observation that some late flowering mutants have increased seed dormancy.…”
Section: Analysis Ofsupporting
confidence: 92%
“…In that case and here in this study, high FT levels are associated with the low dormancy state. A recent study of natural variation in Arabidopsis also showed that late flowering is correlated with higher seed dormancy (38). Again this shows that late flowering is associated with more dormant states, in agreement with our observation that some late flowering mutants have increased seed dormancy.…”
Section: Analysis Ofsupporting
confidence: 92%
“…It would also make evolutionary sense, as seed dormancy and germination timing influence the environment in which subsequent flowering and reproduction occur, and vice versa (16,44,50). An integrated mechanism for coordinating these two major life cycle transitions having significant impacts on fitness and survival would be subject to coselection to optimize (or bet-hedge) both (9,11,43,49,50). Much remains to be done to fully understand these complex interactions between plant life cycles and the environment, but our results demonstrate that DOG1 functions as an important molecular integrator that exerts its effects on developmental phase changes at least in part through miRNAregulated pathways.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, in many plants the transition from vegetative to floral development occurs in response to environmental cues, particularly temperature and day length (6,7). Ecological and evolutionary studies have found that seed germination and flowering traits within species are coadapted across habitat ranges (8)(9)(10)(11). Seed dormancy and germination are regulated primarily by the antagonistic actions of the plant hormones gibberellin (GA; promotive) and abscisic acid (ABA; inhibitory), whose synthesis and action vary in response to environmental signals (12).…”
mentioning
confidence: 99%
“…4), and latitudinal gradients in dormancy observed in A. thaliana and also in the sea beet Beta vulgaris ssp. maritima (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In many species, the timing of germination is controlled by seed dormancy, which is a heritable trait (30,31) that shows evidence of adaptive differentiation. Up to 90% of the plant species in temperate regions produce seeds that are dormant at maturation (31), and intraspecific genetic variation in seed dormancy has been documented along altitudinal (32,33) and latitudinal gradients (34)(35)(36). Moreover, sequence variation in the dormancy gene DELAY OF GERMINATION 1 (DOG1) in Arabidopsis thaliana indicates local adaptation (34), and the level of seed dormancy has been shown to be important for establishment success in novel environments (37).…”
mentioning
confidence: 99%